A Modified Algorithm-Based Levator Aponeurectomy in Mild to Moderate Congenital Blepharoptosis - Deng, Zhizhong; He, Minyan; Zhou, Xianyu; Qiu, Yucheng; Yang, Jun; Liu, Fei (Aesthetic plastic surgery, 2024)
Background Levator aponeurectomy is a common operation for mild to moderate blepharoptosis. The accuracy of ptosis correction relied on intraoperative judgement when patients were under local anesthesia. For patients who must receive the operation under general anesthesia, it would be an issue to determine how much length of levator aponeurosis to shorten. To solve this issue, we collected data from patients who underwent the operation under local anesthesia and concluded an algorithm. Methods This single-center, prospective bivariate regression study allocated patients of mild to moderate congenital blepharoptosis who received levator aponeurectomy under local anesthesia. Preoperative MRD1 and levator function, intraoperative amount of levator aponeurotic shortening, and postoperative MRD1 were measured. The follow-up period was right after the operation. Results Twenty-nine patients were included in this trial. Two subjects exited because of not receiving allocated operation and data of the other 27 subjects (including 34 eyelids) were analyzed. A scatter diagram was drawn where x axis referred to levator function and y axis referred to the ratio of the amount of shortening of levator aponeurosis over the height of MRD1 correction. Linear regression showed y = − 0.2717*x + 5.026, R 2 = 0.8553. Conclusion A modified algorithm to predict the amount of shortening of levator aponeurosis based on levator function and height of ptosis correction was concluded with better accuracy and clinical feasibility. Level of Evidence IV This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .